Evaluasi Kebijakan Publik Pemerintah Kota Batam Dalam Meningkatkan Kualitas Pendidikan - Firiansyah, Iranda; Khoiri, M.; Haldy, Muhammad (Prodi Ilmu Administrasi Negara, 2024)
Education is an important component in developing quality and competitive human resources (HR), especially in industrial areas like Batam. The inequality in the quality of education between city centers and peripheral areas, as well as the lack of educational facilities in a number of schools, hinder efforts to produce a workforce that is ready to compete at the global level. This article aims to analyze the evaluation and challenges in the Batam City Government Policy regarding Improving the Quality of Education, secondly to analyze the Education Budget Policy in Batam City, and to analyze the Education Program Innovation in Batam City. This study applies a qualitative approach with a review of scientific literature and analysis of secondary data from official documents and the media. Research findings indicate the significance of policies that prioritize adequate education budget allocation, program innovation such as e-learning, and collaboration with the private sector. The main challenge faced is the disparity between the central and peripheral areas of Batam regarding access to quality education and increasing teacher professionalism. Thus, an assessment of education policies that prioritize improving educational facilities, training and funding is very important to support sustainable economic growth and reduce social disparities in Batam.